2014
DOI: 10.1186/bf03351695
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pi 2 magnetic pulsations observed at the CPMN stations: A review of the STEP results

Abstract: From analyses of magnetic data from the Circum-pan Pacific Magnetometer Network (CPMN) stations, we can find the following wave characteristics of Pi 2 magnetic pulsations. (1) Pi 2 pulsations observed on the ground are an ensemble of various hydromagnetic modes excited at high, middle, low, and equatorial latitudes. Each mode exhibits its own propagation (timing) and spatial illumination. (2) There are apparent longitudinal propagation and latitudinal time delays of the maximum Pi 2 magnetic energy among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 37 publications
5
115
1
Order By: Relevance
“…It suggests that the SCW did not sufficiently develop to exhibit typical magnetic bay signature during the present event. Contrary to such small magnitude of the bay variations, the amplitude of Pi2 for each station was comparative or larger than that of the normal amplitude reported by Yumoto et al [2001] for each latitudinal and local time region. The above observational facts bring up a question: How was the D component oscillation generated by such small magnitude SCW?…”
Section: Ground Pi2 Signatures Interpreted By Previously Reported Pi2mentioning
confidence: 65%
See 4 more Smart Citations
“…It suggests that the SCW did not sufficiently develop to exhibit typical magnetic bay signature during the present event. Contrary to such small magnitude of the bay variations, the amplitude of Pi2 for each station was comparative or larger than that of the normal amplitude reported by Yumoto et al [2001] for each latitudinal and local time region. The above observational facts bring up a question: How was the D component oscillation generated by such small magnitude SCW?…”
Section: Ground Pi2 Signatures Interpreted By Previously Reported Pi2mentioning
confidence: 65%
“…Olson [1999] summarized that the Pi2 signal is associated with the following two fundamental processes occurred at substorm expansion onsets: (1) response of the high-latitude ionosphere to sudden generation of field-aligned currents in association with the disruption of cross-tail current in the plasma sheet and (2) impulse response of the inner magnetosphere to the compressional waves that are generated at substorm onset. Yumoto et al [2001] summarized that the Pi2 pulsations observed on the ground consist of five hydromagnetic wave components excited by the above two processes. Olson [1999] and Yumoto et al [2001] stated that a compressional pulse (fast mode wave) causes field line resonances and surface waves at the plasmapause as well as cavity waves in the inner magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations